Task-Dependent and Independent Synchronous Activity of Monkey Hippocampal Neurons in Real and Virtual Translocation - Hori, Etsuro; Tabuchi, Eiichi; Matsumura, Nobuhisa; Ono, Taketoshi; Nishijo, Hisao (Frontiers in Behavioral Neuroscience, 2011)
Previous neurophysiological and behavioral studies relate hippocampal functions to place learning and memory, and encoding of task (or context)-specific information. Encoding of both task-specific information and own location is essential for episodic memory and for animals to navigate to reward-related places. It is suggested that different neural circuits with different assemblies of different hippocampal neurons are created in different environments or behavioral contexts for the hippocampal formation to encode and retrieve episodic memory. To investigate whether synchronous activity of hippocampal neurons, suggesting functional connectivity between those neurons, is task and position dependent, multiple single unit activities were recorded during performance of real and virtual translocation tasks. The monkey moved to one of 4 reward areas by driving a cab (real translocation) or by moving a pointer on a monitor (virtual translocation). Of 163 neuron pairs, significant peaks in cross-correlograms (CCRs) were observed in 98 pairs. Most CCRs had positive peaks within 50 ms. Task-dependent CCRs were observed in 44% of the neuron pairs, and similarly observed in both the real and virtual translocation tasks. These CCRs were frequently observed in pyramidal vs. pyramidal neuron pairs with positive peak and peak shift. However, no consistent patterns of peak polarity, peak shift, and neuronal types were seen in task-independent CCRs. There was no significant difference in frequency of CCR peaks between real and virtual translocation tasks. These results suggest that the task-dependent information may be encoded by interaction among pyramidal neurons, and the common information across tasks may be encoded by interaction among pyramidal neurons and interneurons in the hippocampal formation. These neuronal populations could provide a neural basis for episodic memory to disambiguously guide animals to places associated with reward in different situations.